Disability, health and retirement in the United Kingdom - James Banks; Richard Blundell; Antoine Bozio; Carl Emmerson (Institute for Fiscal Studies (IFS), 2011)
This paper examines changes in health and disability related transfers in the UK over the last thirty years, and describes how they are related to changes in labour force participation. The objective is to present a comprehensive description of the reforms to the institutional setting, along with available time series coming from administrative data on benefit receipt, cross-section or panel data on self-reported health and their interactions with labour force status. By providing systematic evidence on institutions and data, we hope to help future research providing a fuller picture of the trends over this period. We also present evidence on the impact of two large reforms to disability benefits in the UK. @The NBER Bulletin on Aging and Health provides summaries of publications like this. You can sign up to receive the NBER Bulletin on Aging and Health by email. Over the last thirty years pathways to retirement have changed substantially in the UK. They have been dominated by spells of unemployment in the late 1970s, with then an increased importance of disability spells from the mid-1980s onwards. At the end of the period the direct route from work to retirement was increasingly more common. General economic conditions seem to have been important driving forces during the entire period. In contrast changes in health do not seem to provide convincing explanations for these trends: mortality has been falling over the period without any apparent link to the share of the population reporting ill health or disability or to the number claiming benefits. We also find evidence that recent reforms have had some impact. The halting of the previous growth in the rate of in-flow onto disability benefits in the mid-1990s coincided with the implementation of a major reform. Evidence from the pilots of the Pathways-to-Work programme in 2003-2005 suggests that those moving onto disability benefits moved off these benefits faster than they would otherwise have done as a direct result of the programme
Keywords: 330; National Bureau of Economic Research web site; Arbeitsmarkt; Arbeitslosigkeit; Behinderte Arbeitskräfte; Gesundheit; Flexible Altersgrenze; Großbritannien